Using systems thinking for agricultural research for development to transform food systems in the global South - Valencia Leñero, Eva M.; Ewell, Hanna; Schiller, Katharina; Woltering, Lennart; Bailey, Arwen (Utrecht University, 2024)
This study investigates the role of systems thinking tools in bridging the gap between theoretical knowledge and practical implementation for sustainable transformation, with a focus on the agri-food sector. Drawing from an assessment of various toolkits and guidelines, it highlights the potential of systems approaches in translating complex sustainability theories into actionable strategies. While these tools provide valuable frameworks for understanding and engaging with multifaceted challenges, such as novelty, innovation, and collaboration, they also reveal certain limitations and gaps. The analysis highlights the diversity in available toolkits, tailored to different sectors and stakeholders, and underscores their role in fostering organizational change and facilitating collaboration. However, it identifies challenges such as the predominance of tool development in the Global North, linguistic barriers, and a lack of consensus on defining systems and addressing long-term processes and uncertainties. Furthermore, the study explores opportunities and challenges for the application of systems thinking tools within a case study of CGIAR, emphasizing the need for a paradigm shift towards integrated, inclusive, and locally-relevant approaches. It calls for the institutionalization of systems thinking approaches and the development of comprehensive yet accessible tools to guide researchers in examining their innovations within broader systems, fostering collaboration, and maximizing impact. Despite limitations in sample size and scope, this research offers insights into the potential of systems thinking toolkits and guidelines as part of the processes to drive sustainable transformations in agri-food systems. It underscores the importance of comprehensive tailored-made toolkits that can guide researchers and agricultural development practitioners in applying systems approaches to advance agricultural innovation for sustainability transitions in their own fields, contexts and sectors.